Research progress on the role of PTEN deletion or mutation in the immune microenvironment of glioblastoma - Du, Leiya; Zhang, Qian; Li, Yi; Li, Ting; Deng, Qingshan; Jia, Yuming; Lei, Kaijian; Kan, Daohong; Xie, Fang; Huang, Shenglan (Frontiers in Oncology, 2024)
Recent advances in immunotherapy represent a breakthrough in solid tumor treatment but the existing data indicate that immunotherapy is not effective in improving the survival time of patients with glioblastoma. The tumor microenvironment (TME) exerts a series of inhibitory effects on immune effector cells, which limits the clinical application of immunotherapy. Growing evidence shows that phosphate and tension homology deleted on chromsome ten (PTEN) plays an essential role in TME immunosuppression of glioblastoma. Emerging evidence also indicates that targeting PTEN can improve the anti-tumor immunity in TME and enhance the immunotherapy effect, highlighting the potential of PTEN as a promising therapeutic target. This review summarizes the function and specific upstream and downstream targets of PTEN-associated immune cells in glioblastoma TME, providing potential drug targets and therapeutic options for glioblastoma.